Pengaruh Gaya Kepemimpinan Transformasional, Dan Work-Life Balance Terhadap Kinerja Pegawai (GEMA EKONOMI, 2023)
In the current era of globalization, science and technology (science and technology) has a significant influence on various developments in the field of employment, so that competition between companies cannot be avoided. To obtain this requires control and support from leaders and balanced work in order to produce better performance. This study aims to determine and analyze the effect of Transformational Leadership Style, and Work-life Balance on Employee Performance at the Customs and Excise Service Office of Type C Sintete. This research is an associative research and the type of data used is quantitative, as well as primary data obtained from interviews and distributing research questionnaires to the Office of Customs and Excise Customs and Excise Type C Sintete. The sample in this study amounted to 60 employees of the Office of Customs and Excise Supervision and Services Type C Sintete with saturated sampling. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that simultaneously Transformational Leadership Style and Work-life Balance have a significant effect on Employee Performance at the Customs and Excise Service Office Type C Sintete, while partially each variable shows Transformational Leadership Style and Work-life Balance has a positive and significant effect on employee performance at the Customs and Excise Office of Type C Sintete.